Matching Contributions for Pensions : A Review of International Experience - Hinz, Richard (Washington, DC: World Bank, 2012)
Establishing robust, equitable, and effective social protection is essential to reducing poverty and boosting prosperity at all levels of development. The demographic transition that has already transformed most high-income societies will exert similar and growing pressures on others, reinforcing the role of pensions and savings for old age as a central pillar of social protection systems. One possible solution that has emerged in recent years that offers the potential to overcome this challenge is the provision of contribution matches to provide an immediate and powerful incentive for participation in pension saving systems. Originating in several high-income settings there are now a number of innovations and substantial experience in low-income countries in using this design to stimulate coverage and savings. This experience now provides a rich opportunity for learning, not just from the longer experience of a few high-income countries but also the more meaningful South-South learning across developing countries.This volume, which reviews the experience with matching pension contributions across the range of countries that have used the design, makes an initial, but critically important investment in this learning process. The description and analysis of this experience which is the product of partnership and collaboration across many public and private institutions provide an invaluable early assessment of the design to inform policy makers and practitioners as well as serve as a model for the kind of cooperation that will be required to address this difficult challenge. At the World Bank, we look forward to being part of this learning process of how to best provide old-age security for all.